The Effects of Indoxyl Sulfate and Oxidative Stress on the Severity of Peripheral Nerve Dysfunction in Patients with Chronic Kidney Diseases - Yun-Ru Lai; Ben-Chung Cheng; Chia-Ni Lin; Wen-Chan Chiu; Ting-Yin Lin; Hui-Ching Chiang; Chun-En Aurea Kuo; Chih-Cheng Huang; Cheng-Hsien Lu (MDPI AG, 2022)
Pieces of evidence support the view that the accumulation of uremic toxins enhances oxidative stress and downstream regulation of signaling pathways, contributing to both endothelial microangiography and cell dysfunction. This study is to address the impact of protein-binding uremic toxins on the severity of peripheral nerve function in patients with chronic kidney disease (CKD). Fifty-four patients with CKD were included in the Toronto Clinical Neuropathy Score (TCNS), nerve conduction study (NCS), and laboratory studies including protein-binding uremic toxin (indoxyl sulfate [IS] and p-cresyl sulfate [PCS]), oxidative stress (Thiol and thiobarbituric acid reacting substances [TBARS]), and endothelial dysfunction (serum intercellular adhesion molecule 1 [sICAM-1] and serum vascular adhesion molecule 1 [sVCAM-1]) at enrollment. We used composite amplitude scores (CAS) to analyze the severity of nerve conductions on peripheral nerve function. TCNS and CAS were higher in the diabetic CKD group (p = 0.02 and 0.01, respectively). The NCS revealed the compound muscle action potential of ulnar and peroneal nerves and the sensory nerve action potential of ulnar and sural nerves (p = 0.004, p = 0.004, p = 0.004, and p = 0.001, respectively), which was found to be significantly low in the diabetic group. CAS was significantly correlated with age (r = 0.27, p = 0.04), urine albumin-creatinine ratio (UACR) (r = 0.29, p = 0.046), free-form IS (r = 0.39, p = 0.009), sICAM-1 (r = 0.31, p = 0.02), sVCAM-1 (r = 0.44, p < 0.0001), TBARS (r = 0.35, p = 0.002), and thiols (r = −0.28, p = 0.045). Linear regression revealed that only TBARS and free-form IS were strongly associated with CAS. The mediation analysis shows that the sVCAM-1 level serves as the mediator between higher IS and higher CAS. IS and oxidative stress contribute to the severity of peripheral nerve dysfunction in patients with CKD, and chronic glycemic impairment can worsen the conditions.